Kajian Hermenutika Teks Lagu Tradisional Cik-Cik Periok di Daerah Kalimantan Barat - Zakarias Aria Widyatama Putra; Yudhistira Oscar Olendo; Mastri Dihita Sagala (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
This hermeneutic study research seeks to translate traditional songs from West Kalimantan, particularly thos of Cik-Cik Periok. The purpose of the application research is to study Cik-Cik Periok’s song historical context, an interpreter’s interpretation of meaning, and cultural context in order to find the deep context. The method for expressing subsequent interpretations uses qualitative methods with a Schleiermacher romantic hermeneutic approach that focuses on grammatical interpretation, technical interpretation, and cultural context. The data collected comes from in-depth interviews with ethnographers, writers, and language academics. The hermeneutical study discovered interpretations and translation results in the historical context of the Sambas people’s daily life in the West Kalimantan region; the technical interpretation of the song text is the attitude of respect implied to newcomers in the area; and the cultural context associated with character education Cik-Cik Periok’s song.